Students’ Learning Outcomes on Genre-Based Approach Implementation in Teaching A Recount Text Writing - Alwasilah, Yuzaki Adam (Ma'soem University, 2025)
This study examines students' learning outcomes in writing when a genre-based approach (GBA) is applied. Conducted at a private school in Bandung, West Java, Indonesia, the research utilized the teaching phase and analysis of students' written texts to gather data. The findings indicate that most students perceived the instructional methods and stages employed in teaching recount texts as clear and effective. In terms of learning outcomes, students demonstrated notable improvements in their written texts, particularly in text structure and linguistic elements, from the first draft to the second. However, some students showed little to no progress in their writing. This highlights the need for future research to design engaging and comprehensible learning activities. Overall, the implementation of the genre-based approach significantly enhanced the writing skills of the majority of students.